2021
DOI: 10.3390/ijms22094988
|View full text |Cite
|
Sign up to set email alerts
|

A Salivary Odorant-Binding Protein Mediates Nilaparvata lugens Feeding and Host Plant Phytohormone Suppression

Abstract: Odorant-binding proteins (OBPs) typically act as transporters of odor molecules and play an important role in insect host location. Here, we identified an OBP in brown planthopper (BPH) Nilaparvata lugens salivary glands via transcriptome sequencing. Real-time quantitative PCR and Western blotting analysis results showed that NlugOBP11 was highly expressed in salivary glands and secreted into rice plant during feeding, suggesting that it assists in BPH feeding on rice. Functional analysis in N. lugens saliva r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…The abundant expression of OBPs genes in insect antennae suggests that it is mainly involved in the olfactory function of insects( Yang et al 2016 , Pelosi et al 2018 ). Other studies have also shown high expression of OBPs in male antennae, suggesting involvement in courtship ( Liu et al 2022 , Chen et al 2018a , b ). Hence, we hypothesize that OBP10 is likely involved in courtship as well as olfactory function of B. odoriphaga of B. odoriphaga .…”
Section: Discussionmentioning
confidence: 76%
“…The abundant expression of OBPs genes in insect antennae suggests that it is mainly involved in the olfactory function of insects( Yang et al 2016 , Pelosi et al 2018 ). Other studies have also shown high expression of OBPs in male antennae, suggesting involvement in courtship ( Liu et al 2022 , Chen et al 2018a , b ). Hence, we hypothesize that OBP10 is likely involved in courtship as well as olfactory function of B. odoriphaga of B. odoriphaga .…”
Section: Discussionmentioning
confidence: 76%
“…For example, two calcium-binding proteins, regucalcin and calmodulin, were reported to inhibit calcium-derived callose formation in the phloem during aphid feeding (Reviewed by van Bel and Will, 2016). An odorant-binding protein (OBP11) identified in saliva of Nilaparvata lugens (brown planthopper), was shown to promote feeding by suppressing the production of salicylic acid - a phytohormone that regulates plant defense against pathogens - in rice plants (Liu et al, 2021). Unique to TSWV-infected females, ATP-generating and amino acid-producing intermediates of the tricarboxylic acid pathway, evidence of active energy generation, were enriched in the saliva.…”
Section: Discussionmentioning
confidence: 99%
“…After the activation of the chemosensory receptors, odorant degrading enzymes (ODEs) rapidly degrade the odorants [ 10 ]. However, other studies have demonstrated that the expression of odorant-binding proteins in other tissues such as the salivary glands, fat body, or midgut may be associated with alternative physiological functions in the insect [ 11 , 12 , 13 ]. Some OBPs , for instance, have been found to relate to innate immunity, pesticide resistance, and anti-inflammation [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%